Computational analysis for efficient thermal transportation of ternary hybrid nanofluid flow across a stretching sheet with Cattaneo-Christov heat flux model - Wei Li; Shan Ali Khan; Muhammad Shafqat; Qamar Abbas; Taseer Muhammad; Muhammad Imran (Case Studies in Thermal Engineering)
Hybrid nanomaterials greatly improve thermal systems by increasing thermal conductivity, storing energy more efficiently, and customizing thermo-mechanical features. Binary/ternary hybrid nanofluids are important in industries such as biomedicine, transportation, and pharmaceuticals because of their excellent thermophysical properties. This study aims to examine the impacts of Cattaneo-Christov (CC) heat flux on the laminar flow of mixed convective (Al2O3−Ag−CuO/water) ternary hybrid nanofluid across a stretching sheet with heat generation. Current investigation examines the nanoparticles Al2O3−Ag−CuO that were dispersed in water. The effect of magnetic field, thermal radiation, Thomson and Troian velocity slip and convective condition is also scrutinized. The significance of different shapes (sphere, cylindrical and blade) of nanoparticles in ternary hybrid nanofluid is also analyzed. The phenomenon were designed as partial differential equations. These are condensed to system of ODEs via similarity transformations. The bvp4c solver in MATLAB is utilized to compute the numerical solution of current problem. From the results it is concluded that velocity field is reduced with larger magnetic field. Furthermore it is concluded that the temperature distribution in increases with enlarging the thermal relaxation parameter. The temperature distribution is enhanced with thermal radiation parameter. We anticipate significant implications for engineering, medicine, and biomedical technology from this innovation. This model can be utilized to research biological systems, clinical procedures, nanopharmacological medication delivery mechanisms, and the use of nanotechnology in the treatment of disorders like cholesterol.